Trauma Exposure and Mental Health Problems Among Adults in Central Vietnam: A Randomized Cross-Sectional Survey - Do, Trang Thi Hanh; Correa-Velez, Ignacio; Dunne, Michael P. (Frontiers in Psychiatry, 2019)
Background: There is relatively little evidence about the psychological and social impacts of trauma exposure in the general population in East Asian countries. Vietnam has a long history of war and poverty, is prone to natural disasters and has high mortality related to traffic accidents. The mental health systems may be inadequate to cope with the resultant trauma. Objectives: This research examines the lifetime prevalence of single and multiple traumas and the association between trauma exposure and depression, anxiety and post-traumatic stress disorder (PTSD) among a randomly selected sample of the adult population in Thua Thien-Hue province in central Vietnam. Methods: Six hundred and eight Vietnamese adults aged 18 years or older participated in the survey. The main tools in the face-to-face interview included the Life Event Checklist (LEC) to measure trauma exposure, the Hospital Anxiety and Depression Scale (HADS) and the PTSD Checklist for DSM-IV (PCL-IV). Hierarchical multiple logistic regression was used to examine associations between trauma exposure and mental health. Results: Forty seven percent of the participants experienced at least one traumatic event in their lifetime and about half of these people were exposed to multiple traumas. The prevalence of depression, anxiety, and PTSD symptoms among the total sample was 12.7, 15.5, and 6.9%, respectively. Prevalence of PTSD among those reporting trauma exposure was 14.8%. Exposure to a higher number of trauma types was associated with increased risk of having depression, anxiety, and PTSD symptoms. Interpersonal traumas were strongly associated with symptoms of all three mental disorders while non-interpersonal traumas were only associated with depressive symptoms. Conclusion: Our findings indicate high burden of lifetime trauma and mental ill health in the adult population of central Vietnam and show a cumulative effect of multiple traumas on symptoms of the three mental disorders. Interpersonal trauma appears to have a more harmful effect on mental health than non-interpersonal trauma. Efforts to improve mental health in Vietnam should focus on reducing risk of preventable interpersonal trauma in every stage of life, and more broadly, ensure greater availability of trauma-sensitive mental health programs and services.